Redesigning customer support services for electronic resources: The case of UDSM library - Wema, Evans F (University of Dar es Salaam Library Journal, 2019)
This paper reports on a study conducted at the University of Dar es Salaam library to determine whether or not library customers are satisfied with services related to access and use of electronic resources. A total of 70 postgraduate students filled out an online questionnaire with both open and close-ended questions; however, 53 of the respondents returned the filled-in questionnaires. The findings revealed that most users were at the coursework stage and are mainly interested in various web-based electronic resources for the purpose of answering assignment questions while a few are interested in using subscribed to journal articles to assist with their research work and writing up dissertations. The findings further revealed that while there is generally satisfaction with how librarians offered services related to access and use of electronic resources, a number of challenges were encountered including lack of appropriate communication skills among librarians who handle customers, limited human resources, slow response rates from librarians and problems related to limited number of computers, slow Internet connectivity, electricity power supply. It was recommended that library services related to access and use of electronic resources should be re-designed to enable librarians serve customers better by utilizing appropriate customer-service related skills.